Seasonal vitamin D status and endothelial function in healthcare workers - (:unkn) unknown (My University, 2016)
0

Background/aim: Healthcare workers have long working hours indoors and are at risk of vitamin D deficiency. The aim of this study was to determine seasonal vitamin D status and its relationship with early atherosclerotic markers, endothelial function, and carotid intima-media thickness (CIMT) in healthcare workers of Marmara University Hospital, İstanbul. Materials and methods: One hundred and ninety healthy volunteer healthcare workers and 66 nonmedical volunteers of Marmara University Hospital were included in the study and 25-hydroxyvitamin D (25(OH)D), calcium, intact parathyroid hormone (PTH), endothelial function, and CIMT were measured twice during winter and summer seasons. Results: Mean vitamin D levels were 20 ng/mL in summer and 16.4 ng/mL in winter. Out of the healthcare workers, 48.9% were vitamin D deficient at the end of summer and 71.5% in winter. Flow-mediated dilation (FMD) values were similar in both groups in both seasons; however, FMD values of 64 healthcare workers in summer were significantly higher than in winter. Serum 25(OH)D was positively associated with FMD (r = 0.1797, P = 0.0441) and negatively correlated with serum PTH (r = 0.2459, P < 0.0001). A negative correlation between FMD and serum PTH (r = 0.1757, P = 0.0473) was observed. Conclusion: Vitamin D levels of healthcare workers are very low, even in summer time. Healthcare workers must be considered a group at major risk for vitamin D deficiency.
Keywords: Cerrahi